Auditoria ambiental na gestão pública : hospital da Universidade Federal de Sergipe - Feitosa, André Luís Oliveira (2011)
Human action, greatly through their social organizations, track a path separate from the balance and harmony of the biophysical conditions that sustain life on Earth. In this sense, new forms of management that best respond to the social and environmental needs are being developed and applied. Gradually the public administration in Brazil has introduced the concepts of environmental management systems in their structure. Among the actions that make up these systems is the Environmental Audit. The audit is an important management tool that has been strengthened since the Administrative Reform of the 1990s, and the Environmental Audits one of the newest segments, which emerged from the larger mission of helping managers to better understand the weaknesses of their institutions, to ensure compliance with its policies, contribute to the improvement of management controls and provide qualitative information to support decision making that will influence the medium to long term all of the organizational culture of the organization on issues concerning the environment, whether the public authority is the entity private. In this context, we investigate the means by which public managers can be guided to structure an entity Environmental Audits with great social responsibility linked to health and education - the Hospital of the Federal University of Sergipe. To do so, as the object of research, methodological tools were employed grounded in phenomenology, and his character had finalistic exploratory, descriptive and explanatory. We found that the institution has the material resources to the implementation of Environmental Audits. Human resources are the most difficult point for the implementation of Environmental Audits, given the lack of human resources as the institution, aggravated by the expansion process and internalization. However, overcome this obstacle and set up the audit team, the Federal University of Sergipe has the opportunity to introduce Environmental Audits on campus not only the health of the city of Aracaju, but in all units which would place in line with good social and environmental practices that have been adopted by the Institutions of Higher Education and encouraged by the very forefront Federal Public Administration in Brazil.